COVID‐19: A Global Threat to the Nervous System - Koralnik, Igor J. (Ann Neurol, 2020)
In less than 6 months, the severe acute respiratory syndrome‐coronavirus type 2 (SARS‐CoV‐2) has spread worldwide infecting nearly 6 million people and killing over 350,000. Initially thought to be restricted to the respiratory system, we now understand that coronavirus disease 2019 (COVID‐19) also involves multiple other organs, including the central and peripheral nervous system. The number of recognized neurologic manifestations of SARS‐CoV‐2 infection is rapidly accumulating. These may result from a variety of mechanisms, including virus‐induced hyperinflammatory and hypercoagulable states, direct virus infection of the central nervous system (CNS), and postinfectious immune mediated processes. Example of COVID‐19 CNS disease include encephalopathy, encephalitis, acute disseminated encephalomyelitis, meningitis, ischemic and hemorrhagic stroke, venous sinus thrombosis, and endothelialitis. In the peripheral nervous system, COVID‐19 is associated with dysfunction of smell and taste, muscle injury, the Guillain‐Barre syndrome, and its variants. Due to its worldwide distribution and multifactorial pathogenic mechanisms, COVID‐19 poses a global threat to the entire nervous system. Although our understanding of SARS‐CoV‐2 neuropathogenesis is still incomplete and our knowledge is evolving rapidly, we hope that this review will provide a useful framework and help neurologists in understanding the many neurologic facets of COVID‐19. ANN NEUROL 2020;88:1–11 ANN NEUROL 2020;88:1–11